Health students’ literacy on sexually transmitted infections (Research, Society and Development, 2025)
Sexually transmitted infections (STIs) represent a global public health challenge and require effective prevention and treatment strategies. Objective: To assess the knowledge of health students about STIs, with an emphasis on prevention and treatment. Methodology: Quantitative, descriptive, cross-sectional study conducted in an academic setting. Data collection was performed using the STD-KQ (Sexually Transmitted Disease Knowledge Questionnaire), considering 50% correct answers as sufficient knowledge about STI. Data analysis was performed using SPSS software (25.0). The research was submitted to the Ethics Committee of the University of Paraná (CAAE 92514725.4.0000.0109). Results: Questionnaires from 51 people were analyzed, most of whom were female (90.2%) and aged between 21 and 25 years (47.1%). In terms of academic distribution, 54.9% were beginners and 45.1% were graduates. In the assessment of STI literacy, graduates had a higher percentage of correct answers compared to beginners, with statistically significant differences in questions about transmission, prevention, and treatment. Some questions showed no relevant difference, indicating that certain content is not yet fully consolidated in undergraduate education. Conclusion: The research shows that advances in academic training contribute to STI literacy, but reveals persistent gaps in undergraduate students' knowledge. It highlights the importance of improving teaching strategies throughout undergraduate studies and encouraging new research that explores innovative methodologies to strengthen the prevention and treatment of sexually transmitted infections.